Empirical Evaluation of User Experience Using Lean Product and Process Development: A Public Institution Case Study in Indonesia - A'ang, Subiyakto; Rohadatul, Aisy; Bernadus, Gunawan Sudarsono; Manorang, Sihotang; Didik, Setiyadi; Asrul, Sani (2021)
The convenience, speed, accuracy, security are the four main indicators of information quality that are concerning for people to be able access information in a public institution dashboard system. To find out whether the data displayed on the system is easily understood by the users, an empirical evaluation study might be indispensable to be performed. Evaluating user experience is one way to know whether a system is in accordance with user needs or not, whether related to data, interfaces, or system performance. This study assessed user experiences based on the product pyramid and its development process in the case of a public dashboard system in a public institution in Indonesia. The empirical experiment was conducted by 15 participants used a scenario that was deliberately designed and then gave answers to the single ease question (SEQ) and the system usability scale (SUS). The results show that SEQ measurement obtained almost 5.7 amount of score which indicates the application measurement results reach an easy level. The SUS results demonstrated that the system was in the acceptable category with a score around 81.3 Although the findings of the study might not contribute theoretically, it may demonstrate a practical consideration for the stakeholders, in terms of the next system development stage.